An Overview of Scientific Reproducibility: Consideration of Relevant Issues for Behavior Science/Analysis - Laraway, Sean (Perspect Behav Sci, 2019)
For over a decade, the failure to reproduce findings in several disciplines, including the biomedical, behavioral, and social sciences, have led some authors to claim that there is a so-called “replication (or reproducibility) crisis” in those disciplines. The current article examines: (a) various aspects of the reproducibility of scientific studies, including definitions of reproducibility; (b) published concerns about reproducibility in the scientific literature and public press; (c) variables involved in assessing the success of attempts to reproduce a study; (d) suggested factors responsible for reproducibility failures; (e) types of validity of experimental studies and threats to validity as they relate to reproducibility; and (f) evidence for threats to reproducibility in the behavior science/analysis literature. Suggestions for improving the reproducibility of studies in behavior science and analysis are described throughout.